A new series of Cd(ii) metal–organic architectures driven by soft ether-bridged tricarboxylate spacers: synthesis, structural and topological versatility, and photocatalytic properties. Issue 40 (24th August 2018) - Gu, Jin-Zhong; Cai, Yan; Wen, Min; Shi, Zi-Fa; Kirillov, Alexander M.
Abstract : Two multifunctional, ether-bridged tricarboxylic acids were used as unexplored and highly versatile building blocks for the hydrothermal generation of eight new cadmium(ii ) metal–organic architectures. Abstract : Two multifunctional, ether-bridged tricarboxylic acids, 2-(4-carboxylphenoxy)terephthalic acid (H3 cpta) and 2-(3, 5-dicarboxylatobenzyloxy)benzoic acid (H3 dbba), were used as unexplored and highly versatile building blocks for the hydrothermal generation of a novel series of cadmium(ii ) metal–organic architectures. These were formulated as [Cd(μ-Hcpta)(phen)(py)] n (1 ), [Cd3 (μ5 -cpta)2 (phen)3 ]·8H2 O n (2 ), [Cd3 (μ5 -cpta)2 (2, 2′-bipy)3 ]·6H2 O n (3 ), [Cd(μ3 -cpta)(Hbpa)]·2H2 O n (4 ), [Cd6 (μ4 -cpta)2 (μ6 -cpta)2 (H2 biim)2 (H2 O)6 ]·5H2 O n (5 ), [Cd3 (μ4 -cpta)2 (μ-prz)(H2 O)4 ] n (6 ), [Cd3 (μ4 -dbba)2 (phen)3 ]·H2 O n (7 ), and [Cd3 (μ3 -dbba)2 (2, 2′-bipy)3 (H2 O)3 ]·2H2 O n (8 ) on the basis of single-crystal X-ray diffraction, elemental analysis, FTIR, PXRD, and TGA data. Products1–8 were assembled in the presence of N-donor crystallization mediators selected from pyridine (py), 1, 10-phenanthroline (phen), 2, 2′-bipyridine (2, 2′-bipy), bis(4-pyridyl)amine (bpa), 2, 2′-biimidazole (H2 biim), or piperazine (prz). The nature of the crystallization mediator and/or the type of principal tricarboxylate building block have a significant effect on the structural diversity, dimensionality, and topology of the resulting cadmium-organic architectures. These span from 1D (1, 8 ) and 2D (7 ) coordination polymers to 3D metal–organic frameworks (2–6 ) with intricate topologies (3, 4, 5T64 in2 and3, utp (10 3 )-d in4, 3, 4, 4T9 in6 ) that also include unprecedented types in5 and7 . Besides, MOF6 features a 3D + 3D two-fold interpenetrated framework. Luminescent and photocatalytic properties of selected materials were investigated, showing that coordination polymer7 is a promising photocatalyst for the UV-light-driven degradation of methylene blue as a model organic dye pollutant. Moreover, products7 and8 are the first examples of structurally characterized coordination compounds derived from H3 dbba.